ANALISIS PERBEDAAN KADAR BLOOD UREA NITROGEN (BUN) DAN KADAR SERUM CREATININE (SC) PADA PENDERITA DIABETES MELITUS TIPE 2 DENGAN PROFIL LIPID NORMAL DAN DISLIPIDEMIA DI RUMAH SAKIT UMUM PUSAT SANGLAH PERIODE JANUARI-DESEMBER 2014 - Widyaningsih, Made Ayu; Lestari, AA Wiradewi; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; Vol 5 No 10 (2016): E-jurnal medika udayana)
T2DM and dyslipidemia are the two conditions that are often found together. Blood sugar levels which are not controlled can lead to the increasing of fatty substances level in the blood and accelerate the arteriosclerosis. The consequences of dyslipidemia and inflammation will cause a decrease in blood supply to the kidneys, interfere the glomerulus filtration rate (GFR), and then followed by increased blood urea nitrogen (BUN) and serum creatinine (SC). Goal of this study to prove the existence of differences in levels of BUN and SC in patients with T2DM with normal lipid profiles and dyslipidemia in Sanglah Hospital. A cross-sectional analytic study was completed with a total sample of 160 T2DM patients treated at Sanglah Hospital. Data were collected through consecutive sampling method from the medical record of January-December 2014 and analys with Mann Whitney Test.The mean differences of BUN levels are significant between patients with normal lipid profile compare with hypertriglyceridemia (p = 0.002), hypercholesterolemia (p = 0.005), and hyper-LDL (p = 0.013) in T2DM patients. There are also significant mean differences of SC levels among patients with normal lipid profiles compare with hypertriglyceridemia (p = 0.000), and hypercholesterolemia (p = 0.006) in T2DM patients. Our study highlights that there are significant differences of BUN levels in T2DM patients with normal lipid profile compare with hypertriglyceridemia, hypercholesterolemia, and hyper-LDL patients and significant differences of SC levels in T2DM patients with normal lipid profile compare with patients who have hypertriglyceridemia and hypercholesterolemia (p <0.05).
Keywords: T2DM, Lipid Profile, Dyslipidemia, BUN, SC